The spring migration of two Bar-tailed Godwit Limosa lapponica populations in Sweden - Green, Martin; Blomqvist, Sven; Lindström, Åke (Ornis Svecica, 2003)
The regional distribution and timing of spring passage of the Bar-tailed Godwit Limosa lapponica in Sweden is reported (160,300 observed birds in 1976—1995). Birds were observed in most provinces, with the highest concentrations in southernmost Sweden. Timing of passage was bimodal, with distinct peaks in the middle and end of May, suggesting that two separate populations are passing. The peak in mid-May probably refers to the European population wintering in north-western Europe and bound for breeding areas in Scandinavia, Finland and westernmost Russia. The later peak most likely represents the Afro-Siberian population, on passage from West Africa to northern Siberia. The European birds were recorded over most of Sweden, whereas the Afro-Siberian birds were concentrated to the southern part. More European than Afro-Siberian birds were seen, even though the European population is considerably smaller. Presumably, a higher proportion of European than of Afro-Siberian birds stops in southern Sweden. The time pattern of Bar-tailed Godwit migration is compared with the passage of other arctic migrants previously reported.